ZAKAT MANAGEMENT POST OF BIRTH UU NO. 23 OF 2011 CONCERNING MANAGEMENT OF ZAKAT - Rahmadi Indra Tektona; Ikarini Dani Widiyanti; Tiya Ningrum Rahayu (Universitas Islam Negeri Mataram, 2020)
Management of zakat after birth No. 23 of 2011, zakat management is the planning, implementation, and supervision of the collection and distribution and utilization of zakat. The purpose of this study is to find out and understand the substantial differences in the management of zakat in Law No.38 of 1999 with Law no. 23 of 2011. The research method used is the type of juridical normative research (legal research). The results of this study there are some differences in the previous and present laws, namely the naming change, the abolition of BAZDA to BAZNAS and formed directly by the minister, the former Amil Zakat Institute formed by the community now formed by Islamic community organizations and its arrangements are increasingly complex, the Government now has the highest position in managing zakat compared to the community and only people who have permission to manage zakat. There are administrative and criminal sanctions.